Dual effects of gossypol on human hepatocellular carcinoma via endoplasmic reticulum stress and autophagy. (August 2019) - Zhang, Guang; Wang, Zhongxia; Chen, Weibo; Cao, Yin; Wu, Junyi; Qiang, Guanghui; Ji, Anlai; Wu, Junhua; Jiang, Chunping
Abstract: Treatment outcomes for hepatocellular carcinoma (HCC) remain unsatisfactory, and effective new therapeutic methods are urgently needed. Gossypol has been shown to have an anti-HCC effect, but the underlying mechanism requires further study. In this study, we found gossypol inhibited HCC cells in vitro and in vivo. Typical apoptosis was induced in HCC cells. Dilated ER and autophagosomes were observed by electron microscopy, and the activation of the unfolded protein response and autophagy markers suggested that gossypol induced both ER stress and autophagy. C/EBP homologous protein was the key factor that led to apoptotic cell death, whereas inositol-requiring enzyme 1α and eukaryotic initiation factor 2α played a protective role. Autophagy protected the cells from ER stress-related apoptosis. Both in vitro and in vivo studies indicated that inhibition of autophagy enhanced the anti-HCC effect of gossypol. Taken together, ER stress is the molecular mechanism underlying gossypol-induced apoptosis and autophagy. Gossypol exhibits anti-HCC activity primarily through the activation of apoptosis. However, gossypol-induced autophagy protects HCC cells from ER stress. Therefore, a combination therapy of gossypol and autophagy inhibitors may lead to an enhanced anti−HCC effect.